FEATURES OF DEVELOPMENT OF PRESCHOOL CHILDREN - Ashirbayeva Shohsanam Shoikromovna (Web of Journals Publishing, 2025)
This article is illuminated on the basis of features and stages of development of preschool children analytical ideas.
Keywords: Preschool children, tetraining, development, preschool childhood period, devaluation.